Pengembangan Media Pembelajaran Interaktif Berbasis Game Sub Materi Anatomi Fisiologi Pada Kelas X SMK Labschool UNESA 1 Surabaya - Anggraini, Iin Hayyu Findy; Novia Restu Windayani; Octaverina Kecvara Pritasari; Biyan Yesi Wilujeng (Jurnal Tata Rias, 2026)
Game-based learning media is considered to increase student interest in learning because it combines elements of entertainment and education in one teaching tool. This study aims to create interactive learning media based on games that can help students understand the subtopic of skin anatomy and physiology in a fun and interactive way. The method applied is the ADDIE development model. The results of the assessment by material experts and media experts indicate that the designed interactive game-based learning media is included in the "very appropriate" classification with a material examination result of 4.8 and a media result of 4.57. The average student response to the media showed the highest score of 4.9. In addition, student learning achievement also increased with a pretest score of 0.120 and a posttest score of 0.105. These findings prove that this interactive learning media based on games can be beneficial for learning, especially for theoretical subjects such as skin anatomy and physiology. By using this media, students can develop a greater level of curiosity and understanding in addition to participating in learning.